Multicenter retrospective cohort of EUS-guided anterograde pancreatic duct access - Motomura, Douglas; Irani, Shayan; Larsen, Michael; Kozarek, Richard A; Ross, Andrew S; Gan, S Ian (Endoscopy International Open, 2023)
Background and study aims Pancreatic duct (PD) cannulation may be difficult during conventional endoscopic retrograde cholangiopancreatography (ERCP) due to underlying pathology, anatomical variants or surgically altered anatomy. Pancreatic access in these cases previously necessitated percutaneous or surgical approaches. Endoscopic ultrasound (EUS) allows for an alternative and can be combined with ERCP for rendezvous during the same procedure, or for other salvage options.Patients and methods Patients with attempted EUS access of the PD from tertiary referral centers between 2009 and 2022 were included in the cohort. Demographic data, technical data, procedural outcomes and adverse events were collected. The primary outcome was rendezvous success. Secondary outcomes included rates of successful PD decompression and change in procedural success over time.Results The PD was accessed in 105 of 111 procedures (95 %), with successful subsequent ERCP in 45 of 95 attempts (47 %). Salvage direct PD stenting was performed in 5 of 14 attempts (36 %). Sixteen patients were scheduled for direct PD stenting (without rendezvous) with 100 % success rate. Thus 66 patients (59 %) had successful decompression. Success rates improved from 41 % in the first third of cases to 76 % in the final third. There were 13 complications (12 %), including post-procedure pancreatitis in seven patients (6 %).Conclusions EUS-guided anterograde pancreas access is a feasible salvage method if retrograde access fails. The duct can be cannulated, and drainage can be achieved in the majority of cases. Success rates improve over time. Future research may involve investigation into technical, patient and procedural factors contributing to rendezvous success.